2006
DOI: 10.1158/0008-5472.can-05-2328
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Receptor Inhibition Enhances Adenoviral Infectability of Carcinoma Cells via Up-Regulation of Coxsackie and Adenovirus Receptor in Conjunction with Reversal of Epithelial-Mesenchymal Transition

Abstract: Expression of the Coxsackie and Adenovirus Receptor (CAR) is frequently reduced in carcinomas, resulting in decreased susceptibility of such tumors to infection with therapeutic adenoviruses. Because CAR participates physiologically in the formation of tight-junction protein complexes, we examined whether molecular mechanisms known to down-regulate cellcell adhesions cause loss of CAR expression. Transforming growth factor-B (TGF-B)-mediated epithelial-mesenchymal transition (EMT) is a phenomenon associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 33 publications
6
58
0
1
Order By: Relevance
“…Similar results have recently been reported by others, who showed that LY2109761 induces the expression of the Coxachie and adenovirus receptor (CAR), a part of the tight-junction protein complexes involved in the EMT process. 22 This is also consistent with our previous work, in which TGF-␤1 stimulated a more invasive and aggressive phenotype of constitutively noninvasive HCC cells, promoting the EMT via down-regulation of E-cadherin. 10 E-cadherin is a cell-cell adhesion molecule strongly implicated in the invasiveness of different malignancies including HCC, and down-regulation of this molecule has been proposed to have a role in facilitating tumor recurrence and progression.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have recently been reported by others, who showed that LY2109761 induces the expression of the Coxachie and adenovirus receptor (CAR), a part of the tight-junction protein complexes involved in the EMT process. 22 This is also consistent with our previous work, in which TGF-␤1 stimulated a more invasive and aggressive phenotype of constitutively noninvasive HCC cells, promoting the EMT via down-regulation of E-cadherin. 10 E-cadherin is a cell-cell adhesion molecule strongly implicated in the invasiveness of different malignancies including HCC, and down-regulation of this molecule has been proposed to have a role in facilitating tumor recurrence and progression.…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory cytokines, such as TNFα, TGFβ and IFNγ, are known to compromise epithelial integrity by repressing cell-cell adhesion molecules (e.g. E-cadherin, ZO-1 and CAR) [36][37][38]. Reduced expression of CAR or E-cadherin was most evident among carcinomas under progression, which was frequently accompanied by cytokine response in vivo [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 While the exact molecular mechanisms leading to loss of CAR expression remain unclear, data from others and our laboratory suggest mechanisms underlying loss of CAR expression, such as promoter hypermethylation and repression through activation of Raf-MEK-ERK and TGFb signaling. [24][25][26][27][28] Thus, pharmacological receptor restoration using inhibitors of these pathways may increase the efficiency of adenovirus agents in vivo. 25,27 An alternative route to overcome CARdependent intrinsic resistance to adenovirus infection has been developed that is based on modifying adenovirus capsid proteins in order to retarget the virus to other receptors that are more consistently expressed on cancer cells.…”
Section: Discussionmentioning
confidence: 99%